2017
DOI: 10.1002/cssc.201601843
|View full text |Cite
|
Sign up to set email alerts
|

Selective Hydrogenation of Nitriles to Primary Amines by using a Cobalt Phosphine Catalyst

Abstract: A general procedure for the catalytic hydrogenation of nitriles to primary amines by using a non-noble metal-based system is presented. Co(acac) in combination with tris[2-(dicyclohexylphosphino)ethyl]phosphine efficiently catalyzes the selective hydrogenation of a wide range of (hetero)aromatic and aliphatic nitriles to give the corresponding amines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(63 citation statements)
references
References 69 publications
2
61
0
Order By: Relevance
“…84 On the other hand, Beller and co-workers observed the accumulation of Co(I) species in a related catalytic system utilizing a Co(III) metal precursor for nitrile hydrogenation. 88 Similar intermediacy of Co(I) species was also observed by Milstein and co-workers, who addressed the use of a series of Co(II) precatalysts in dehydrogenative coupling. The authors found that Co(I) was likely the actual active species in catalysis that was formed upon reaction of the Co(II) precatalyst with NaHBEt 3 additive.…”
Section: Metal Oxidation State -Cobalt and Manganesesupporting
confidence: 67%
See 2 more Smart Citations
“…84 On the other hand, Beller and co-workers observed the accumulation of Co(I) species in a related catalytic system utilizing a Co(III) metal precursor for nitrile hydrogenation. 88 Similar intermediacy of Co(I) species was also observed by Milstein and co-workers, who addressed the use of a series of Co(II) precatalysts in dehydrogenative coupling. The authors found that Co(I) was likely the actual active species in catalysis that was formed upon reaction of the Co(II) precatalyst with NaHBEt 3 additive.…”
Section: Metal Oxidation State -Cobalt and Manganesesupporting
confidence: 67%
“…More importantly, carboxylic acids, that are more challenging for a homogeneous catalyst to hydrogenate compared to their esters, 8 could be converted under the same conditions in the absence of any additives at a lower catalyst 86,87 based catalysts for carboxylic acid hydrogenation, which at some instances requires higher temperatures or metal loadings compared to the Co case. Later work by Beller and co-workers 88 disclosed the use of polydentate phosphine ligands in Co-catalyzed hydrogenation of nitriles to primary amines. 88 It was found that the polydentate phosphine ligand identical to that in M-Co-2 gave only a low activity in the target reaction, whereas the in situ formed M-Co-3 based on a tetradentate phosphine allowed quantitative yields in benzonitrile hydrogenation at 100 1C, 5% mol Co loading and 30 bar H 2 .…”
Section: Catalysis: Activity Reaction and Substrate Scopesmentioning
confidence: 99%
See 1 more Smart Citation
“…30 Beller and co-workers reported on the tripodal phosphorus ligand II employed in Ru-catalyzed nitrile hydrogenation achieving high selectivities for a range of aliphatic and aromatic monoamines under mild and additive-free conditions, 31 whereas no activity in this reaction was observed for a cobalt-Triphos catalyst. 32 Moreover, the intrinsic separation issue of homogeneous catalysts remains a limiting factor for many applications. 35 To Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Current researches about the reduction of nitriles are mostly conducted with pressurized hydrogen ( Srimani et al., 2012 , Tokmic et al., 2017 , Chakraborty et al., 2017 , Mukherjee et al., 2017 , Adam et al., 2016 , Adam et al., 2017 , Cao et al., 2016 , Elangovan et al., 2016 , Chakraborty and Milstein, 2017 , Ji et al., 2017 , Yoshimura et al., 2018 ). However, direct hydrogenation is always labeled as a harsh synthetic process due to the explosive nature of hydrogen ( Schafer et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%